Students’ reasoning patterns in solving statistical data problems at the junior high school level: An APOS perspective - Betty Kusumaningrum; Muhammad Irfan; Yova Ayu Puspita; Esti Harini; Elyas Djufri; Luc Bergman (Jurnal Elemen, 2026)
Many students face challenges in reasoning through statistical data problems; however, little is known about how their thinking processes develop through different cognitive stages. A qualitative descriptive design was employed to explore students’ reasoning patterns in solving statistical data problems through the lens of Action, Process, Object, and Schema (APOS) theory. This study was conducted with seventh-grade students at a public junior high school in Kulon Progo, Indonesia. Data were collected through written tests and semi-structured interviews and were analyzed using coding techniques aligned with the APOS indicators. The results show that students with correct answers demonstrated conceptual reasoning and progressed through all APOS stages, whereas those with incorrect answers showed fragmented understanding and failed to complete the cognitive sequence. This study contributes to mathematics education by extending the APOS theory to statistical data representation at the secondary level.